FROM TRADITION TO COMPREHENSION: LEVERAGING THE WISDOM OF 'KENTONGAN' IN DISCOVERY LEARNING TO FOSTER SCIENTIFIC LITERACY - Septiana, Adela; Tyas, Rizki Arumning (Universitas Tanjungpura, 2025)
Scientific literacy is essential for equipping students to solve real-world problems and engage meaningfully with scientific concepts. However, Indonesian students continue to exhibit low performance in international assessments, including PISA and TIMSS. This study aims to examine the effectiveness of the discovery learning model enriched with the local wisdom of kentongan